Rancang Bangun Sistem Kontrol dan Monitoring Data Turbin Angin Berbasis Website Menggunakan Raspberry Pi 3B+ - Meiki Eru Putra; Zulkifli Amin; Islahuddin Islahuddin; Sanny Ardhy (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
Indonesia has considerable wind energy potential. Energy generation system performance can be monitored and controlled through the Internet of Things (IoT) technology. However, research and development of IoT technology in wind turbines in Indonesia is still low. Therefore, in this study, the author seeks to conduct research related to the development of a website-based wind turbine control and data monitoring system. This research uses a 3 blade horizontal axis wind turbine (NACA 2410). The monitoring system uses the Raspberry Pi 3B + microcontroller and several sensor devices such as the IR LM393 speed sensor to measure wind speed and shaft rotation speed, and the INA219 current-voltage sensor to measure the voltage and current of a 350 Watt DC generator. The website was created using the Laravel 5.8 PHP framework and Chart.js. Furthermore, the sensor calibration process and system testing are carried out. Based on the test results, it was found that the monitoring data system was functioning properly. The data has been successfully sent to the server and can be monitored in real-time via the website. Based on the results of the IR LM393 sensor calibration test, the linear regression equation y = 0.7881x + 13.837, and the value of R2 = 0.9934 is obtained. And the value of R2 = 0.9934 indicates that the sensor calibration process is well correlated. The results of testing the control system and monitoring of wind turbine data monitored through the website for 1 x24 show that the highest wind potential occurs at 13.00 to 14.00 WIB, namely at a wind speed of 3.74 m / s.